The Effectiveness Of Health Promotion Using Counseling Media/Lectures On Increasing Knowledge Of Health Facility Deliveries At PKM Kresek - Wiwin Widiawati; Achmad Fauzi (CV. Inara, 2024)
Background: The coverage of delivery assistance at Indonesian health facilities in 2019 was 88.8%, while delivery assistance by health personnel had also reached 90.9%, meaning that there were still around 2% of deliveries assisted by health personnel not at the Health Facility.Purpose of Writing: To find out the effectiveness of health promotion using counseling/lecture media on increasing knowledge of delivery of health facilities at PKM Kresek. Research Methods: This type of quasi-experimental research with a one group pretest post-test design, the population of this study were all pregnant women who visited the Kresek Health Center, totaling 60 people. statistical test using Wilcoxon. Research Results: There was a significant difference between the values before and after health promotion, namely p=0.029 (p<0.05), which means that health promotion using media counseling/lectures is effective in increasing knowledge of delivery of health facilities. Conclusions and Suggestions: It is hoped that the results of this study will further improve health promotion using media counseling/lectures about childbirth in health care facilities to motivate the community in terms of utilizing delivery facilities at the Puskesmas.